2019
DOI: 10.1111/tpj.14290
|View full text |Cite
|
Sign up to set email alerts
|

OsMYB108 loss‐of‐function enriches p‐coumaroylated and tricin lignin units in rice cell walls

Abstract: Breeding approaches to enrich lignins in biomass could be beneficial to improving the biorefinery process because lignins increase biomass heating value and represent a potent source of valuable aromatic chemicals. However, despite the fact that grasses are promising lignocellulose feedstocks, limited information is yet available for molecular-breeding approaches to upregulate lignin biosynthesis in grass species. In this study, we generated lignin-enriched transgenic rice (Oryza sativa), a model grass species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…To comprehensively understand the molecular and biological cellular pathway, recent progress in CRISPR/Cas9-mediated genome editing could be a vital tool, as lignin-enriched transgenic rice by using CRISPR/Cas9-targeted mutagenesis of the transcriptional repressor OsMYB108 was achieved. Rice mutants of OsMYB108 -knockout revealed a considerable rise in the expression levels of lignin biosynthetic genes by enhancing lignin deposition in culm cell walls [113]. Hence, this study suggested that scientists should have to further investigate the regulation and complexity of biochemical pathways that counter lodging problem.…”
Section: Morphological Traits and Their Responses Under Lodging Stmentioning
confidence: 99%
“…To comprehensively understand the molecular and biological cellular pathway, recent progress in CRISPR/Cas9-mediated genome editing could be a vital tool, as lignin-enriched transgenic rice by using CRISPR/Cas9-targeted mutagenesis of the transcriptional repressor OsMYB108 was achieved. Rice mutants of OsMYB108 -knockout revealed a considerable rise in the expression levels of lignin biosynthetic genes by enhancing lignin deposition in culm cell walls [113]. Hence, this study suggested that scientists should have to further investigate the regulation and complexity of biochemical pathways that counter lodging problem.…”
Section: Morphological Traits and Their Responses Under Lodging Stmentioning
confidence: 99%
“…Blastx searches showed that several of them ( Supplementary Table S7) share high similarity with phenylpropanoid-related MYBs in Arabidopsis, including AtMYB112 (17 genes), a regulator of anthocyanin biosynthesis (Lotkowska et al, 2015), and AtMYB36 (11 genes) that directly and positively regulates the expression of genes involved in the formation of Casparian strips (Kamiya et al, 2015), a root diffusion barrier made of exclusively of lignin (Naseer et al, 2012). In addition, we also found putative orthologs of repressors of phenylpropanoid biosynthesis ( Supplementary Table S7), including the Arabidopsis AtMYB4 and AtMYB7 (eight and three genes, respectively) (Wang et al, 2020) and their corresponding orthologs OsMYB108 in rice (Miyamoto et al, 2019), ZmMYB31/42 in maize (Agarwal et al, 2016), and PvMYB4 in switchgrass (Shen et al, 2012). These MYBs are members of subfamily 4 of the R2R3-MYB family that function as transcriptional repressors of monolignol and flavonoid biosynthesis (Agarwal et al, 2016;Wang et al, 2020).…”
Section: The Expression Of Regulators Of Scw Deposition and Pcd Is Inmentioning
confidence: 81%
“…Repression is also supplied by the MYB G4 clade and are the best characterised in grasses. These include ZmMYB11/31/ 42, PvMYB4/32, and OsMYB108, which are orthologous to AtMYB4/32 (Zhao & Bartley, 2014;Rao & Dixon, 2018;Miyamoto et al, 2019). These were first described in a grass as direct repressors of lignin gene expression (Fornal e et al, 2006;Sonbol et al, 2009).…”
Section: Reviewmentioning
confidence: 99%